2017
DOI: 10.1001/jamacardio.2016.3956
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 30-Day All-Cause Readmissions in Patients Hospitalized for Heart Failure

Abstract: Use of a number of ML algorithms did not improve prediction of 30-day heart failure readmissions compared with more traditional prediction models. Although there will likely be further applications of ML approaches in prognostic modeling, our study fits within the literature of limited predictive ability for heart failure readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(235 citation statements)
references
References 14 publications
12
215
1
7
Order By: Relevance
“…These results replicate our previous findings10, 11, 12 and provide further evidence regarding the utility of this biomarker in the prediction of recurrent hospitalizations, an end point of clinical significance that currently cannot be predicted accurately with standard prognostic factors 3, 4…”
Section: Discussionsupporting
confidence: 89%
“…These results replicate our previous findings10, 11, 12 and provide further evidence regarding the utility of this biomarker in the prediction of recurrent hospitalizations, an end point of clinical significance that currently cannot be predicted accurately with standard prognostic factors 3, 4…”
Section: Discussionsupporting
confidence: 89%
“…Missing data for the remaining 86 variables were handled using mean (numeric variables) or most common value (non‐numeric variables) imputation. We trained a random forest model to predict survival up to 1 year after hospital discharge or at an outpatient clinic visit 18, 19. The random forest algorithm was chosen because it can be applied to a data set with mixed variable types, performs well on data sets with large numbers of variables, is not prone to overfitting, and allows estimation of variable importance.…”
Section: Methodsmentioning
confidence: 99%
“…The Random Forest (RF) machine learning algorithm is a process of fitting a series of classification and regression trees to the data 18. A tree is constructed by first taking a single bootstrap sample of the data.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent, methodologically sound study, Frizzell et al showed that machine learning approaches performed poorly compared with traditional statistical methods in the context of congestive heart failure readmission prediction 41. As the authors themselves conclude, results of their large-scale machine learning attempt to predict readmissions are largely not concordant with both earlier and emerging findings 9 42.…”
Section: Introductionmentioning
confidence: 98%